Adjuvant radiotherapy for breast cancer. Which patients benefit from DIBH (deep inspiration breath-hold)? Adjuvante Strahlentherapie beim Mammakarzinom - Schönecker, S.; Schäfer, A.; Pazos, M.; Corradini, Stefanie (Chirurgische Praxis, 2021)
Breast radiotherapy in deep inspiration breath-hold (DIBH) can significantly reduce the dose exposure of the heart in most left-sided breast cancer patients. For this reason, heart-sparing radiotherapy techniques should always be evaluated in all left-sided breast cancer patients in general. Risk modelling studies have shown that irradiation in DIBH can not only reduce long-term cardiovascular toxicities, but also reduce the risk for secondary lung cancer. Thus, according to the principle of optimising radiation protection (ALARA principle:»as low as reasonably achievable«), this technique offers the possibility of reducing the radiation exposure of the heart and lungs to a minimum.
CRIS-Team Scopus Importer:2025-10-13
Keywords: adjuvant radiotherapy; breast cancer; cardiotoxicity; DIBH; surface scanners